Actores del “sector medio desconocido”. La gobernanza global entre bastidores - G. Weiss, Thomas; Wilkinson, Rorden (El Colegio de México A.C., 2022)
This article focuses on the vast number of people who make global governance happen. It probes the role of the unknown people in the “middle” who are largely absent from scholarly gaze: professionals, service teams, and others who act behind the scenes. They are not at the top of public and private organizations (“global governors” in the literature), but they keep the lights on. They accomplish the policy, operational, and support work to move the needle of global governance institutions of all varieties from the local to global. These largely invisible and unheard populations — at least in the scholarly and policy literatures — make global governance work. The “missing middle” is not confined to the everyday contributions of professionals in intergovernmental secretariats because contemporary global governance is not synonymous with international organization, but concerns networked forms of public authority that may or may not include secretariats or states.